Space vehicle mechanisms elements of successful design - Conley, Peter; Packard, Douglas; Purdy, William (John Wiley & Sons, 1998)
Space Vehicle Mechanisms: Elements of Successful Design brings together accumulated industry experience in the design, analysis, and application of the mechanical systems used during space flight.